2012
DOI: 10.1007/s11999-011-2203-5
|View full text |Cite
|
Sign up to set email alerts
|

A New High-flexion Knee Scoring System to Eliminate the Ceiling Effect

Abstract: Background Various scoring systems document improvement after TKA, but most are associated with a ceiling effect that may fail to distinguish between patients having different levels of knee function after TKA. We therefore developed a new scoring system for patients with higher levels of flexion to eliminate ceiling effects observed with current systems. Questions/purposes The purposes of this study were (1) to determine whether the high-flexion knee score eliminates the ceiling effect, (2) to assess the vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 26 publications
2
50
0
2
Order By: Relevance
“…In patient demographics, there was an inordinately larger proportion of females (80%) in this study, but this is likely due to a greater utilization of health care and life expectancy of females than males, in addition to the higher prevalence of OA. This was similarly reflected in other studies in the Asian population [16,20]. It was also interesting to note that the mean BMI of patients was high (28.2 ± 5.7) with 74% of the study population being overweight or obese.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In patient demographics, there was an inordinately larger proportion of females (80%) in this study, but this is likely due to a greater utilization of health care and life expectancy of females than males, in addition to the higher prevalence of OA. This was similarly reflected in other studies in the Asian population [16,20]. It was also interesting to note that the mean BMI of patients was high (28.2 ± 5.7) with 74% of the study population being overweight or obese.…”
Section: Discussionsupporting
confidence: 85%
“…All parameters show statistically significant improvement (P < .05) with the exception of GH component of SF-36 achieving only a mean difference of 2 points (P ¼ .221). In addition, it is noted that even though statistical [20]. Tables 3 and 4 show the correlation between changes in KSS and OKS scores vs the changes in the summary and subscale scores of SF-36, respectively.…”
Section: Comparison Of Postoperative Outcomes At 2-year Follow-upmentioning
confidence: 96%
“…In the present study, group B performed superior to group A in terms of postoperative activity improvement, while the improvement in the Kujala score in group A was better than in group B; however, similar KSS and WOMAC scores were recorded in the two groups. There are two hypotheses for this similarity between the groups: one, knee mobility may be taken into account in the KSS and WOMAC scores, compensating for the deficiency in the Kujala score in group B; two, the KSS and WOMAC clinical scoring systems may have been subjected to a ceiling effect [43], resulting in the scoring systems not being sensitive enough to determine between-group differences.…”
Section: Discussionmentioning
confidence: 99%
“…While a previous study has shown the subject system was preferred by bilateral subjects over other TKA designs implanted in the contralateral knee [10], scores in the present study were not noticeably different than those reported by for other devices. This was expected, as the ceiling effects of the Knee Society score likely prevent it from being sensitive enough to determine if differences exist between TKA designs [11].…”
Section: Discussionmentioning
confidence: 99%